2022
DOI: 10.1186/s41687-022-00480-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the EQ-5D-Y-5L, EQ-5D-Y-3L and PedsQL in children and adolescents

Abstract: Background There is an increased use of Patient-Reported Outcome Measures (PROMs) in children and adolescents. The aim of this study was to compare the feasibility, concurrent validity and known-group validity of the EQ-5D-Y-3L (Y-3L), EQ-5D-Y-5L (Y-5L) and PedsQL self-report PROMs. Methods Five hundred and fifty children and adolescents, aged 8–15-years, with acute and chronic health conditions and a general population sample were recruited from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…It was hypothesised that EQ-5D-Y-3L dimensions and LSS would show a moderate-to-high correlation with the PedsQL total score [ 72 ]. It was further anticipated that moderate-to-high correlations would be found between corresponding EQ-5D-Y-3L and PedsQL dimensions/items of mobility and physical functioning; looking after myself and physical functioning; usual activities and physical functioning/social functioning; pain or discomfort and physical functioning; worried, sad, or unhappy and emotional functioning [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was hypothesised that EQ-5D-Y-3L dimensions and LSS would show a moderate-to-high correlation with the PedsQL total score [ 72 ]. It was further anticipated that moderate-to-high correlations would be found between corresponding EQ-5D-Y-3L and PedsQL dimensions/items of mobility and physical functioning; looking after myself and physical functioning; usual activities and physical functioning/social functioning; pain or discomfort and physical functioning; worried, sad, or unhappy and emotional functioning [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…The PedsQL and EQ-5D families of instruments offer multiple age-specific versions [ 15 , 16 ]. These versions contain questions pertinent to a child's development, and they have been translated into various languages and are used across different medical disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…ASIAH KASSIM 1 , JENNIFER R. CHEVINSKY 2 , KAREN CHOONG 3 , RAE DUNCAN 4 , SUSANNA ESPOSITO 5 , REBECCA FOSTER 6 , ALLA GUEKHT 7 , ALLISON JAURE 8 , CARRIE MACKENZIE 9 , VIVIENNE MATTHIES-BONN 10 , KAREN MATVIENKO-SIKAR 11 , LORRAINE MCCLOUD 12 , DONNA C MCPARLAND 12 , VICTOR DANIEL MIRON 13 , SRINIVAS MURRHY 14 , SARAH O CONNEL 12 , MARGARET O'HARA 15 , ANNA OGONOWSKA-SLODOWNIK 16 , JANA PAVARE 17 , PAULA ROBERTSON 18 , JEREMY ROSSMAN 19 , OANA SANDULESCU 20 As a result of the Delphi survey, four outcomes met a priori definition for "consensus in" to be included in the core outcome set and eight met the definition of "consensus out" and were excluded from the core outcome set. During the consensus meeting 13 outcomes were discussed: 11 outcomes with no consensus but at least one group voted "in" and two outcomes with no "in" or "out" votes.…”
Section: Pc-cos Children Project Steering Committee Group Authorsmentioning
confidence: 99%
“…To overcome the limitations and improve the psychometric performance of the Y-3L, a version with five response levels (EQ-5D-Y-5L, hereon Y-5L) has been developed [8]. The feasibility of the Y-5L has been confirmed in previous studies, however these studies have suggested that further testing of the psychometric properties of the Y-5L is required on different samples and conditions [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%